2017
DOI: 10.1109/tvcg.2017.2735098
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Cost of Using Augmented Reality Displays

Abstract: This paper presents the results of two cognitive load studies comparing three augmented reality display technologies: spatial augmented reality, the optical see-through Microsoft HoloLens, and the video see-through Samsung Gear VR. In particular, the two experiments focused on isolating the cognitive load cost of receiving instructions for a button-pressing procedural task. The studies employed a self-assessment cognitive load methodology, as well as an additional dual-task cognitive load methodology. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(50 citation statements)
references
References 37 publications
2
45
0
1
Order By: Relevance
“…This is remarkable, as introducing multiple real-time representations to the learning environment also has a distractive potential. The use of smartglasses as technical solution to create AR environments may be assumed to introduce additional EL [17]. This, however, might not be captured by the CLS, as all items related to the factor EL refer to "instructions and/or explanations".…”
Section: Discussionmentioning
confidence: 99%
“…This is remarkable, as introducing multiple real-time representations to the learning environment also has a distractive potential. The use of smartglasses as technical solution to create AR environments may be assumed to introduce additional EL [17]. This, however, might not be captured by the CLS, as all items related to the factor EL refer to "instructions and/or explanations".…”
Section: Discussionmentioning
confidence: 99%
“…In this section, we review the literature on VR and AR as it pertains to HoloLens display technology, applications for use and human-computer interaction (HCI) strengths and limitations. Baumeister et al (2017) describe three technologies for the display of AR. Those technologies include spatial AR (in which displays are fixed and users need not wear or hold a display device), video see-through and optical see-through.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Since an activity experienced in virtual environments is designed to be similar to an activity experienced in the real-world environments (Bach et al 2018;Coppens 2017), it is said that MR with the Microsoft HoloLens may provide beneficial learning and training applications. However, studies indicate that the increased cognitive load associated with the use of the Microsoft HoloLens in simple procedural tasks has a detrimental impact on performance (Baumeister et al 2017). Bach et al (2018) found that continued instruction and practice with the Microsoft HoloLens can lead to improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al [25] developed a system to emulate different FoVs finding out that a 108 Â 82°FoV allowed users to fulfill tasks quicker than using a FoV constrained to 45 Â 30°. The cognitive cost of using different FoVs is evaluated in [26]. Three different devices have been compared to verify whether distinct devices require different cognitive loads in a button-pressing procedural task.…”
Section: Fov In Armentioning
confidence: 99%